Early Mortality on Continuous Renal Replacement Therapy (CRRT): The Prairie CRRT Study. Issue 1 (22nd July 2016) - Prasad, Bhanu; Urbanski, Michelle; Ferguson, Thomas W.; Karreman, Erwin; Tangri, Nav
Background: Patients with acute kidney injury (AKI) requiring renal replacement therapy (RRT) have an increased short-term and long-term risk of mortality. In most North American intensive care units (ICUs), these patients receive continuous renal replacement therapy (CRRT). Objective: We aim to identify clinical and demographic factors associated with mortality within 24 h of initiating CRRT. Design: This paper is a prospective cohort study. Setting: The setting involves three ICUs (12-bed surgical ICU, 10-bed medical ICU, and a 7-bed combined ICU for both medical and surgical patients) of the Regina Qu'Appelle Health Region (RQHR) Saskatchewan, Canada. Patients: The patients were 106 individuals with AKI who were admitted to the ICUs and received CRRT from April 2013 to September 2014. Measurements: Date and time of admission, transfer to, and initiation of CRRT were documented. Demographic data, use of vasoactive medications, ventilator settings, pH, urine output, and chronic disease comorbidities were measured. Methods: The methods involved a stepwise multiple variable logistic regression model using death within 24 h of starting CRRT as the dependent variable, with significant variables derived from univariate analysis as covariates. Results: Of the 2634 patients admitted to the ICUs in the study period (April 2013 to September 2014), 83. 6 % (2201/2634) had no AKI. Two hundred and sixty-nine or 10.2 % of the patients had stage 3 AKI. One hundred six of the 269 patients (40%) were started on CRRT. Of those on CRRT, 66/106 died in the ICU while on CRRT. Seventeen of the 66 patients (26%) died within 24 h of initiating therapy. In univariate logistic regression models, factors associated with early mortality included fraction of inspired oxygen (per 0.1 unit) (OR 1.39, 95 % CI 1.09-1.77); epinephrine dose >10 μg/min (OR 5.81, 95 % CI 1.86-18.16); vasopressin >0.02 μg/min (OR 3.99, 95 % CI 1.07-14.84); and norepinephrine dose >20 μg/min (OR 11.04, 95 % CI 2.38-51.24) which were associated with early mortality. When included in stepwise multivariate logistic regression analysis, only FiO2 (per 0.1 unit) and the dose of norepinephrine of >20 μg/min were independently associated with early mortality. Limitations: The small sample size was a limitation of this study. Conclusion: Patients admitted to the ICU with AKI requiring CRRT have a high risk of early mortality. In these patients, vasopressor use and hypoxia were independently associated with adverse short-term survival.